THE NEED FOR HARMONIZING VALUE ADDED TAX LEGISLATION IN GULF COOPERATION COUNCIL: Harmonizing Value Added Tax Legislation - Tif Said Suhail Al Mazroui; Maathir Mohammed Saud Al Alawi; Mohammed Muneerali Thottoli; Duaa Suleiman Amur Al Hoqani; Noor Talal Hamed Al Shukaili (Constitutionale, 2022)
The elimination of discriminatory value added tax (VAT) laws on commodities are required for the proper functioning of the Gulf Cooperation Council (GCC) single market. The proper functioning of a single market entails the elimination of discriminatory internal VAT regulations of imported goods or services. Hence, the purpose of this study is to empirically examine the need for harmonizing VAT legislation among GCC countries. The data of this study was collected through a variety of sources, including the ministry's website, VAT law for each country, published articles, and other online data sources/websites with regards to VAT. The data were statistically evaluated using Microsoft Excel. The dependent variable in this study is Harmonization. The factors affecting Value Added Tax Legislation are also called independent variables. Through this search, they harmonize VAT legislation in the GCC countries to maximize the effectiveness of tax laws. That helps to know the challenges faced by GCC companies due to discriminatory VAT regulations and double taxation.  There is a need to harmonize VAT legislation in the GCC countries to maximize the effectiveness of tax laws. This study adds value by assessing the present state and the need for harmonizing VAT legislation in the GCC countries. The timely approach of the study will help policymakers, regulators, and practitioners to understand the importance of harmonizing VAT legislation in the GCC.